Metropolitan area delineation and resilience under a public health crisis: Evidence from the Philippines - Yi Jiang; Jade R. Laranjo (Asian Development Bank (ADB), 2024)
We delineate metropolitan areas (MAs) in the Philippines using cellphone user flow data to proxy for daily commutes. The exercise identifies a number of large MAs that are not officially recognized, and different spatial extents for the three officially designated MAs. The urban system aligns more closely with Zipf's Law when the delineated MAs are considered. MAs with a population exceeding 1 million have grown faster than officially defined urban areas as well as the country as a whole. The mobility restrictions adopted during the coronavirus disease (COVID-19) pandemic had profound impacts on the MAs. MAs experienced fragmentation and contraction when mobility was severely restricted in the first few weeks of the outbreak. As restrictions eased, many MAs swiftly rebounded in size with previously separated municipalities reintegrating into the agglomeration. Regression analysis highlights that proximity, administrative boundaries, accessibility, and labor market complementarity between the core and peripheral municipalities are important factors driving MA formation.
Keywords: I18; O18; R12; R58; 330; metropolitan areas; COVID-19; urban resilience; labor market